2017
DOI: 10.3390/ijms18102118
|View full text |Cite
|
Sign up to set email alerts
|

Fisetin Regulates Nrf2 Expression and the Inflammation-Related Signaling Pathway to Prevent UVB-Induced Skin Damage in Hairless Mice

Abstract: Chronic ultraviolet (UV) exposure may cause skin damage, disrupt skin barrier function, and promote wrinkle formation. UV induces oxidative stress and inflammation, which results in extracellular matrix degradation in the dermis and epidermal hyperplasia. Our previous study demonstrated that fisetin exerts photoprotective activity by inhibiting mitogen-activated protein kinase/activator protein-1/matrix metalloproteinases (MMPs) activation. In this study, fisetin was applied topically to investigate its antiph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 39 publications
0
44
0
Order By: Relevance
“…At the end of the experiment, the exposed areas were excised and then immersed in 10% formaldehyde in the PBS. The slides were mounted with a coverslip, stained in hematoxylin and eosin or Masson’s trichrome, and examined under a microscope or applied for immunohistological analysis as previously described [23].…”
Section: Methodsmentioning
confidence: 99%
“…At the end of the experiment, the exposed areas were excised and then immersed in 10% formaldehyde in the PBS. The slides were mounted with a coverslip, stained in hematoxylin and eosin or Masson’s trichrome, and examined under a microscope or applied for immunohistological analysis as previously described [23].…”
Section: Methodsmentioning
confidence: 99%
“…Fisetin also inhibited aflatoxin-B1-induced hepatocellular carcinoma via the downmodulation of oxidative stress and inflammation in rats (Maurya & Trigun, 2016). The tropical application of fisetin prevented UVB-induced inflammation and oxidative stress during skin damage in hairless mice and human lens epithelial cells, respectively (Wu et al, 2017;Yao, Zhang, Zhang, Ye, & Zhu, 2008).…”
Section: Discussionmentioning
confidence: 97%
“…Recently, Nrf2-ARE signalling was proposed as a master regulator of cellular antioxidant activity (Zhang et al, 2019). Similarly, a number of previous studies have shown that fisetin blocks oxidative stress by augmenting the expression of Nrf2 as well as its target antioxidant gene, unravelling the mechanism through which fisetin exerts its antioxidant actions (Lee et al, 2011;Wu et al, 2017;Zhang, Wang, Zhou, Zhu, & Fei, 2018). In agreement with this, we found the increased expression of Nrf2 as well as that of its target genes HO-1 and Gpx-2 in fisetin-treated CS-exposed rats.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The mice were macroscopically observed, and their ears were excised, fixed in 10% formaldehyde, and embedded in paraffin. The skin slides were stained with H&E. Collagen in the skin sections was stained with Masson trichrome and was examined under a microscope, as previously described [24,25].…”
Section: Methodsmentioning
confidence: 99%